2018
DOI: 10.3346/jkms.2018.33.e198
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of CD8+ and CD45RO+ T Cells Infiltration and Beclin1 Expression Levels for Early Postoperative Cholangitis of Biliary Atresia Patients after Kasai Operation

Abstract: BackgroundPostoperative cholangitis is a common but severe complication after Kasai portoenterostomy for biliary atresia (BA). This study aimed to identify its prognostic factors.MethodsTwo sets of liver paraffin-embedded tissue samples were collected from BA patients who received Kasai portoenterostomy (n = 25 and n = 31, respectively). Patients were divided into non-cholangitis and cholangitis groups. The infiltration of CD4+, CD8+, CD45RO+, CD68+ cells and expression of Beclin1 were quantitatively evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Cholangitis not only seriously affects the quality of life of BA children after KPE but also places great economic and psychological burdens on their parents ( 13 ). The effect of cholangitis on NLS is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholangitis not only seriously affects the quality of life of BA children after KPE but also places great economic and psychological burdens on their parents ( 13 ). The effect of cholangitis on NLS is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Cholangitis was defined as the presence of systemic inflammation (fever ≥38.0°C or elevated inflammatory markers, such as the white blood cell [WBC] count and C-reactive protein [CRP] level), with evidence of cholestasis (jaundice aggravates or regresses, stool color becomes lighter or acholic stool reappears, serum total bilirubin and direct bilirubin increases) ( 11 , 12 ). To better explore the relationship between cholangitis and NLS, cholangitis occurring within 1 month after KPE was defined as early cholangitis, and cholangitis occurring 1 month after KPE was defined as late cholangitis ( 6 , 13 ). A frequency of cholangitis ≤3 times within 6 months after KPE was considered to be occasional cholangitis, and a frequency of >3 times was considered to be recurrent cholangitis.…”
Section: Methodsmentioning
confidence: 99%
“…Cholangitis is the most common complication in patients with BA after Kasai surgery, with an incidence of 30%-70% (Gunadi et al, 2018). Several studies have suggested that cholangitis may be a risk factor for poor prognosis in patients with post-Kasai BA (Jiang et al, 2018). Cholangitis can lead to increased cholestasis and accelerated liver injury.…”
Section: Gut Microbiota and Bile Acid Profiles Are Associated With Ja...mentioning
confidence: 99%
“…Biliary atresia (BA) is a rare but life-threatening neonatal disease [ 1 ]. BA is characterized by progressive intra- and extra-hepatic bile duct inflammation and liver fibrosis, which eventually develops into liver cirrhosis and liver failure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%